High-strength, high-toughness steel for mining chains and method for manufacturing the same
Patent Information
- Application Number
- JP2026518186
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-09-27
- Publication Date
- 2026-10-14
Smart Images

Figure 2026534269000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to the technical field of chain steel, and more specifically to high-strength, high-toughness mining chain steel and a method for producing the same. [Background technology]
[0002] Mining link chains are essential components used in mechanized coal mining within mines, primarily serving as power transmission chains for scraper conveyors, scraper transfer conveyors, coal miners, and coal plows. In actual use, mining link chains are required to possess higher strength and toughness, fatigue resistance, and wear resistance to ensure normal operation. Because coal mines are often located underground in humid and corrosive environments, mining link chains typically require good corrosion resistance.
[0003] In conventional technology, the steel used for mining link chains commonly employed in the coal mining industry is typically the chain steel brand specified in "GB / T 10560-2017 Mining Welded Link Chain Steel." Among these, high-strength mining link chain steel is most widely applied under brands such as 23MnNiMoCr54 steel (abbreviated as 54 steel); however, in response to the diverse needs of downstream users in actual applications, major steel mills in China have already developed a series of high-strength mining chain steels.
[0004] Chinese patent publication number CN110714164A ("High-Quality Cr54 Steel for Coal Mine Chain Links and Method for Manufacturing the Same," publication date: November 6, 2020) discloses Cr54 steel for high-quality coal mine chain links. It ensures the weldability of the chain steel and improves the cold brittleness and hot brittleness of the chain steel by introducing carbon equivalent, cold cracking susceptibility coefficient, and hot cracking susceptibility coefficient.
[0005] Chinese patent publication number CN104532143A ("Large-scale high-strength chain steel for mining and method for manufacturing the same," publication date: April 22, 2015) discloses an improved large-scale chain steel for mining. This chain steel has a diameter of 40-100 mm, a yield strength ≥ 980 MPa, a tensile strength ≥ 1180 MPa, an elongation ≥ 13%, a cross-sectional shrinkage rate ≥ 50%, and a Charpy impact energy > 100 J at room temperature.
[0006] Furthermore, there are technologies to optimize steel based on its composition. For example, Chinese patent publication number CN111101078A ("Nickel-free high-strength steel for mining link chains and method for manufacturing the same," publication date: May 5, 2020) discloses a high-strength mining annular chain steel that does not contain the element Ni. It significantly reduces production costs while ensuring mechanical performance by reducing the content of the precious metal element Ni alloy and increasing the content of C, Si, Cr, and Mo alloy elements.
[0007] The above technology primarily optimizes the design of the components to produce steel for mining chains with relatively high strength, improving the wear resistance of the chains, achieving a relatively long service life, and reducing the cost of using the chains.
[0008] However, in actual use, coal mine underground environments are often humid, making it unavoidable that high-strength chains will be affected by environmental corrosion. Furthermore, high-strength chains are subject to high stress and are sensitive to stress corrosion, making them prone to corrosion fatigue failure (low-load brittle fracture that frequently occurs within months, or even days) during the mid-term of use, leading to premature chain failure.
[0009] Based on this, the present inventors aim to provide a novel chain steel with superior overall performance. By optimizing the alloy composition, the present invention not only possesses high strength but also excellent ductility-plasticity consistency and low production costs, effectively solving the problem of the mismatch between strength and ductility present in existing chains that affects their service life. [Overview of the project] [Problems that the invention aims to solve]
[0010] In view of the problem in conventional chains where the mismatch between strength and toughness / plasticity affects the service life, the present invention aims to provide chain steel and a method for manufacturing the same. Specifically, the present invention produces high-strength, high-toughness mining chain steel that combines relatively high strength and toughness / plasticity, as well as good wear resistance and fatigue resistance, by designing the alloy composition and optimizing the manufacturing process. [Means for solving the problem]
[0011] To achieve the above objective, the present invention employs the following technical means.
[0012] A first aspect of the present invention provides a chain steel having the following chemical composition in mass%,: C: 0.19-0.30%, preferably 0.20-0.30%, Si: 0.05-0.6%, preferably 0.21-0.47%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.5-0.9%, Mo: 0.3-0.55%, Ti: 0.015-0.035%, Al: 0.011-0.05%, preferably 0.02-0.05%, B: 0.0015-0.005%, N: 0.002-0.006%, with the remainder being Fe and unavoidable impurities.
[0013] A second aspect of the present invention provides a chain steel comprising, in addition to 90% or more Fe and unavoidable impurities, the following chemical composition in mass percent: C: 0.19-0.30%, preferably 0.20-0.30%, Si: 0.05-0.6%, preferably 0.21-0.47%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.5-0.9%, Mo: 0.3-0.55%, Ti: 0.015-0.035%, Al: 0.011-0.05%, preferably 0.02-0.05%, B: 0.0015-0.005%, N: 0.002-0.006%.
[0014] Preferably, the unavoidable impurities are P ≤ 0.012%, S ≤ 0.01%, O ≤ 0.0015%, and H ≤ 0.00015%.
[0015] Preferably, the chemical composition of the chain steel satisfies the following equation: Ti / (O+2N)=2~4, where Ti, O, and N are the mass percentages of the corresponding elements.
[0016] Preferably, in the steel for the chain, a portion of element B exists in a solid solution state, where the ratio of element B in a solid solution state to the total amount of element B is B 固 / B 総 = 65% to 85%
[0017] Preferably, the microstructure of the steel for the chain consists of tempered martensite and carbides finely dispersed between the lamellae.
[0018] Preferably, the steel for the chain has a yield strength Rp 0.2 ≥1150MPa, tensile strength R m ≥1250 MPa, preferably ≥1293 MPa, elongation A ≥ 13%, cross-sectional shrinkage Z ≥ 50%, and room temperature impact energy A kv It has the performance to satisfy ≥60J.
[0019] A third aspect of the present invention is: (1) A process for manufacturing cast slabs by smelting and continuously casting molten steel, wherein the smelting process involves sequentially performing electric furnace smelting, LF furnace smelting, and vacuum smelting, and in the vacuum smelting process, the settling time of the molten steel before tapping exceeds 10 minutes. (2) A step of obtaining the chain steel by performing rolling, quenching, and tempering processes on a cast slab, wherein the quenching process involves a heating temperature of 850 to 980°C and a holding time of 1 to 4 hours, and the tempering process involves a tempering temperature of 390 to 550°C, preferably 400 to 550°C, more preferably 400 to 450°C, a tempering time of 1 to 3 hours, and water cooling to room temperature after the tempering process. The present invention provides a method for manufacturing the chain steel, including the steel described above.
[0020] Preferably, in the electric furnace smelting process, molten iron and steel scrap are used as raw materials, foamed slag is generated throughout the entire electric furnace smelting process, the end-point carbon content of the molten steel is controlled to 0.06~0.10%, and the tapping temperature of the molten steel is controlled to 1640~1680°C.
[0021] Preferably, in the electric furnace smelting process, the proportion of molten iron in the raw materials is controlled to 30%~60%.
[0022] Preferably, the LF furnace refining process comprises the following steps carried out in sequence: 1) A step of adding lime and fluorite in the initial stage of LF refining to form slag; 2) A step of enhancing deoxidation and desulfurization using aluminum particles or silicon carbide, and replenishing aluminum wire based on the target Al component in the molten steel; 3) A step of adjusting the alloy components and temperature of the molten steel to the target required values before tapping.
[0023] Preferably, in the vacuum refining process, the molten steel after LF refining is subjected to deslagging treatment, vacuum degassing refining is carried out in a VD furnace or an RH furnace, Al is replenished based on the requirements for the chemical composition of the molten steel, and after ensuring that the free oxygen content in the molten steel is less than 5ppm, Ca and ferrotitanium are added, ferroboron is added after 5~10 minutes, and the molten steel composition is adjusted to the target composition.
[0024] Preferably, when performing vacuum degassing refining in the VD furnace or RH furnace, the intense stirring time under the condition that the vacuum degree is less than 67Pa exceeds 10 minutes.
[0025] Preferably, a titanium wire is selected as the ferrotitanium (FeTi), and a boron wire is selected as the ferroboron (FeB).
[0026] Preferably, in the continuous casting process, protective injection of molten steel is employed throughout the entire process, the superheating of the molten steel in the tundish is controlled to 15-30°C, electromagnetic stirring is employed in the crystallizer and at the end of solidification, and a light reduction process of 10-25 mm is employed at the end of solidification to obtain a cast slab.
[0027] Preferably, in the continuous casting process, the continuous casting and drawing speed is 0.42 to 0.8 m / min, preferably 0.5 to 0.8 m / min, with constant drawing speed control employed, the specific water content of the secondary cooling water is 0.3 to 0.5 L / t, and the cast slab is supplied hot or slowly cooled in a slow-cooling pit.
[0028] Preferably, in the rolling process, the cast slab is placed in a heating furnace and heated before being rolled, with the heating temperature controlled to 1150-1250°C, the heating and holding time to 2-6 hours, the rolling start temperature to ≥ 1100°C, and the rolling end temperature to ≥ 850°C.
[0029] Preferably, in the rolling process, the cast slab is removed from the heating furnace, descaled with high-pressure water, and then rolled. After rolling, it is sent to a heat-insulating pit and slowly cooled for 24 hours or more.
[0030] In the chain steel of the present invention, the design principles for each chemical element are as follows. Unless otherwise specified herein, element content is given in mass percent.
[0031] Carbon (C) is an essential element for ensuring the strength of steel. Increasing the carbon content in steel significantly improves its strength by increasing its ability to undergo non-equilibrium structural transformation. In this invention, the quenching and tempering process suppresses the diffusion of carbon in the steel, inducing shear-type martensitic transformation and thereby significantly improving the strength of the steel. However, the carbon content in steel should not be excessively high. Excessively high carbon content adversely affects the plasticity and toughness of the steel and significantly increases the carbon equivalent of the material, worsening the weldability of the steel. Based on this, the carbon content is controlled to 0.19-0.30%, preferably 0.20-0.30%.
[0032] Si: Adding an appropriate amount of Si to steel enhances the stability of austenite during the cooling process and prevents the formation of coarse carbides. However, the Si content in steel should not be excessively high. Excessively high Si content increases the brittleness of the steel. Based on this, the Si content is controlled to 0.05-0.6%, preferably 0.21-0.47%.
[0033] Mn: Adding an appropriate amount of Mn improves the stability of austenite in steel and also enhances the hardenability of the steel. Furthermore, in this invention, Mn can also improve the strength of steel by increasing the strength of martensite in steel through solid solution strengthening. However, the Mn content in steel should not be excessively high. If the Mn content in steel is excessively high, austenite grains tend to grow during quenching heating, making it easier for harmful elements to segregate at grain boundaries. Based on this, the Mn content is controlled to 1.0-1.8%.
[0034] Cr:Cr can improve the hardenability of steel, forming a hardened martensitic structure, which is advantageous for increasing the strength of the steel. Furthermore, Cr carbides can act to slow down grain growth in the heat-affected zone of welded joints, which is very advantageous for the weld structure of chain steel. Adding appropriate amounts of Cr and Ni to steel is advantageous for improving the corrosion resistance of the steel. However, the Cr content in steel should not be excessively high. If the Cr content in steel is excessively high, carbides will be formed during quenching heat treatment, consuming a large amount of C in the steel. Moreover, a large amount of carbides will aggregate at the grain boundaries, reducing the toughness of the material, significantly increasing the carbon equivalent, and reducing the flash welding performance of chain steel. Based on this, the Cr content should be controlled to 0.4-0.8%.
[0035] Ni:Ni can exist in steel in a solid solution state. Ni, when used in combination with Cr, can significantly improve the hardenability of steel. Adding an appropriate amount of Ni to steel reduces the carbon content at the eutectoid point, which is advantageous for increasing the steel's strength. Furthermore, as is clear from the carbon equivalent formula, the coefficient of Ni is small, and its impact on weld performance is minimal. However, Ni is a precious metal element, and excessive addition increases production costs. Therefore, to obtain excellent performance while keeping manufacturing costs low, the Ni content should be controlled to 0.5-0.9%.
[0036] Mo: Mo primarily exists in steel in a solid solution state, providing a solid solution strengthening effect, improving the hardenability of the steel, and causing martensite to form during the quenching process. However, adding excessive amounts of Mo to steel is undesirable. Too much Mo in the steel significantly increases the carbon equivalent of the material, which is detrimental to the flash welding performance of chain steel. Furthermore, since Mo is a valuable alloying element, excessive addition of Mo increases production costs. Based on this, the Mo content is controlled to 0.3-0.55%.
[0037] B: The main role of B is to increase the hardenability of steel, thereby saving rare and expensive elements such as nickel and molybdenum. However, element B is relatively reactive and has a strong affinity for elements such as oxygen and nitrogen, readily forming boron oxide, boron nitride, etc. This causes element B to lose its beneficial properties, leading to greater variability in the hardenability of steel and affecting the performance stability of the steel material. Excessive amounts of B form intermetallic compounds with Fe and become unevenly distributed at grain boundaries, which is detrimental to the toughness of the steel material and tends to increase temper brittleness. Therefore, in the high-strength, high-toughness mining chain steel of the present invention, the content of element B is controlled to 0.0015-0.005%.
[0038] Ti: The element Ti has a very strong affinity for nitrogen, oxygen, and carbon, and has a high precipitation temperature, making it an effective element for fixing nitrogen and oxygen. This prevents the element B in steel from losing its effect of combining with oxygen and nitrogen to improve hardenability. Ti forms a fine precipitate phase in the steel, which can improve the strength and toughness of the steel, especially its impact toughness at low temperatures. However, if the Ti content in the steel is too high, coarse, angular particles are formed during the smelting and solidification process, reducing the impact toughness of the steel. Therefore, in the high-strength, high-toughness steel for mining chains of the present invention, the Ti content is controlled to 0.015-0.035%.
[0039] The main role of Al:Al is deoxidization. Furthermore, A1N, formed by the bonding of A1 and N, can effectively refine the crystal grains. However, the Al content in steel should not be excessively high. An excessively high Al content in steel affects the pourability of the steel and impairs its toughness. Based on this, the high-strength, high-toughness steel for mining chains of the present invention controls the mass percentage Al content to between 0.011 and 0.05%, preferably between 0.02 and 0.05%.
[0040] N:N is an austenite-forming element and an MX-type precipitate-forming element, playing a role in refining the crystal grains. In B-containing steel, the N element in the steel combines with the B element, causing the B in the steel to lose its alloying properties. To avoid the consumption of B element by the N element, it is necessary to strictly control the N element content in the steel. In the high-strength, high-toughness steel for mining chains of the present invention, the mass percentage content of the N element is controlled to be between 0.002% and 0.006%.
[0041] In the chain steel of the present invention, the content of impurity elements, in mass%, satisfies the following requirements: P ≤ 0.012%, S ≤ 0.01%, O ≤ 0.0015%, and H ≤ 0.00015%. P, S, O, and H are all impurity elements in steel, and within the limits of technically permissible conditions, the content of impurity elements in the material should be reduced as much as possible in order to obtain steel materials with better performance and better quality.
[0042] The impurity elements P and S are both unavoidable harmful elements in steel, and both degrade the performance of the steel. While P can improve the corrosion resistance of steel, the overall side effects are greater. Therefore, the content of element P is controlled to 0.012% or less, and the content of element S is controlled to 0.01% or less.
[0043] The impurity element oxygen (O) can form oxides and complex inclusions with elements such as Al, Ti, and B in the steel, which is detrimental to the performance of the steel. Therefore, the oxygen content is controlled to 0.0015% or less.
[0044] The impurity element H aggregates in defects within steel. High-strength steels, especially those with tensile strengths exceeding 1000 MPa, are particularly sensitive to H content. Hydrogen-induced delayed fracture due to element H leads to premature failure of the chain. Therefore, the H content is controlled to 0.00015% or less.
[0045] In other embodiments, steel may also contain other harmful elements such as As, Pb, Sn, Sb, and Bi. Based on the requirements of national laws and standards, the content of these harmful elements should be reduced as much as possible.
[0046] In this invention, by rationally designing the main alloying elements, the performance of the steel is improved by adding element B, the amount of expensive alloys Ni and Mo added is reduced, and the microstructure of the steel is precisely controlled by making full use of the influence of each alloying element and their interactions on the microstructure and mechanical performance. As a result, the high-strength steel of this invention combines relatively high strength and good ductility and plasticity, and also has good wear resistance and fatigue resistance.
[0047] In specific embodiments, in order to ensure that element B in the steel plays its role in a solid solution state, the chain steel of the present invention uses Ti to fix O and N in the steel, and its chemical composition satisfies Ti / (O+2N)=2~4, where Ti, O, and N are substituted with the mass percentage content of the corresponding elements.
[0048] In the proposed technology of this invention, in addition to element C, the strength and toughness of the alloy are adjusted mainly by elements such as Mn, Ni, Mo, Cr, and B to obtain high-strength, high-toughness chain steel. Here, element B is used in place of some of the elements Ni and Mo to reduce the production cost of chain steel. Since element B readily bonds with elements such as N and O in the steel, and thus loses its effect of improving hardenability, a certain amount of element Ti is added to the steel to fix the elements O and N in the steel. When designing the composition, if the Ti / (O+2N) value in the steel is in the range of 2 to 4, the effect of Ti in fixing O and N in the steel is sufficiently exerted, and in order for element B to improve the hardenability of the steel and stably exert its effect as a substitute for elements Ni and Mo, the proportion of element B in a solid solution state in the steel to the total amount of element B in the steel needs to be 65 to 85%. If the Ti / (O+2N) ratio in steel is low, less than 2, the O and N elements in the steel are not completely fixed by Ti and readily combine with the B element in the steel to form boron-containing nitrides or oxides. This can lead to partial or complete loss of B element, causing significant fluctuations in the hardenability of the steel and affecting its usability. If the Ti / (O+2N) ratio in steel is relatively high, exceeding 4, there is an excess of Ti element in the steel. During the solidification and cooling process of the steel, it combines with the C element in the steel, precipitation and growth around TiN as a nucleus, forming large Ti(C,N) particles. Such particles have sharp edges and tend to reduce the impact and fatigue performance of chain steel, making it unsuitable for use in chains.
[0049] Compared to conventional production technologies, the present invention has the following beneficial effects: 1. The high-strength, high-toughness chain steel of the present invention employs a rational chemical composition design combined with an optimized manufacturing process to optimize the reinforcing elements such as Si, Mn, Ni, Cr, and Mo in the steel. By adding a certain amount of element B instead of the expensive alloy elements Ni and Mo, the hardenability of the mining chain steel is improved, while simultaneously controlling the relationship between the content and blending ratio of elements Ti, N, and O in the steel. In addition, the proportion of element B present in a solid solution state in the steel reaches 65-85% of the total amount of element B in the steel, allowing element B to fully exert its effect of effectively improving the hardenability of the steel and preventing fluctuations in the steel's performance. In this invention, a rational quenching and tempering process imparts good plasticity and toughness to the steel; 2. The high-strength, high-toughness chain steel of the present invention has a rational chemical composition and process design in the smelting and rolling processes, a wide process window, is easy to manufacture, and enables mass production and commercial production; 3. The high-strength, high-toughness chain steel obtained by the method of the present invention has good toughness and can be widely applied to fields requiring high-strength steel materials, such as mining and marine construction. [Brief explanation of the drawing]
[0050] Other features, purposes, and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments with reference to the accompanying drawings below. [Figure 1] Figure 1 is a scanning electron microscope image of the high-strength, high-toughness chain steel manufactured in Example 1 of the present invention. [Modes for carrying out the invention]
[0051] To better understand the above technical proposal of the present invention, the configuration of the present invention will be further described below based on examples.
[0052] The present invention provides a chain steel comprising 90% or more Fe and unavoidable impurities, in addition to the following chemical composition by mass: C: 0.19-0.30%, preferably 0.20-0.30%, Si: 0.05-0.6%, preferably 0.21-0.47%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.5-0.9%, Mo: 0.3-0.55%, Ti: 0.015-0.035%, Al: 0.011-0.05%, preferably 0.02-0.05%, B: 0.0015-0.005%, N: 0.002-0.006%.
[0053] Furthermore, the present invention provides a chain steel having the following chemical composition in mass percent: C: 0.19~0.30%, preferably 0.20~0.30%, Si: 0.05~0.6%, preferably 0.21~0.47%, Mn: 1.0~1.8%, Cr: 0.4~0.8%, Ni: 0.5~0.9%, Mo: 0.3~0.55%, Ti: 0.015~0.035%, Al: 0.011~0.05%, preferably 0.02~0.05%, B: 0.0015~0.005%, N: 0.002~0.006%, with the remainder being iron and unavoidable impurities.
[0054] Research has shown that when the composition of steel satisfies the above chemical components and the content satisfies the above range, chain steel exhibits excellent performance. In this invention, unless otherwise specified, the content of components is given in mass percent.
[0055] In the chain steel of the present invention, P, S, O, and H are all impurity elements in the steel. Within the limits of the technical conditions, the content of impurity elements in the material should be reduced as much as possible in order to obtain steel materials with better performance and better quality. Therefore, among the unavoidable impurities, P ≤ 0.012%, S ≤ 0.01%, O ≤ 0.0015%, and H ≤ 0.00015%.
[0056] To ensure that element B in the steel plays its role in a solid solution state, the elements Ti, O, and N in the high-strength, high-toughness chain steel of the present invention should satisfy the following requirements: Ti / (O+2N)=2~4; where Ti, O, and N are the mass percentage content of the corresponding elements.
[0057] In the proposed technology of this invention, in addition to element C, the strength and toughness of the alloy are adjusted mainly by elements such as Mn, Ni, Mo, Cr, and B to obtain high-strength, high-toughness chain steel. Here, element B is used in place of some of the elements Ni and Mo to reduce the production cost of chain steel. Since element B readily bonds with elements such as N and O in the steel, and thus loses its effect of improving hardenability, a certain amount of element Ti is added to the steel to fix the elements O and N in the steel. When designing the composition, if the Ti / (O+2N) value in the steel is in the range of 2 to 4, the effect of Ti in fixing O and N in the steel is sufficiently exerted, and in order for element B to improve the hardenability of the steel and stably exert its effect as a substitute for elements Ni and Mo, the proportion of element B in a solid solution state in the steel to the total amount of element B in the steel needs to be 65 to 85%. If the Ti / (O+2N) ratio in steel is low, less than 2, the O and N elements in the steel are not completely fixed by Ti and readily combine with the B element in the steel to form boron-containing nitrides or oxides. This can lead to partial or complete loss of B element, causing significant fluctuations in the hardenability of the steel and affecting its usability. If the Ti / (O+2N) ratio in steel is relatively high, exceeding 4, there is an excess of Ti element in the steel. During the solidification and cooling process of the steel, it combines with the C element in the steel, precipitation and growth around TiN as a nucleus, forming large Ti(C,N) particles. Such particles have sharp edges and tend to reduce the impact and fatigue performance of chain steel, making it unsuitable for use in chains.
[0058] The steel for the chain has a yield strength Rp 0.2 ≥1150MPa, tensile strength R m ≥1250 MPa, elongation A ≥ 13%, sectional shrinkage Z ≥ 50%, and room temperature impact energy A kv It has the performance to satisfy ≥60J.
[0059] Furthermore, the present invention provides a method for manufacturing the chain steel. This manufacturing method has a simple production process. The manufactured high-strength, high-toughness chain steel possesses excellent toughness. The following describes the aforementioned method for manufacturing chain steel as an example. Specifically, it employs electric furnace smelting, LF furnace smelting, vacuum smelting, continuous casting, rolling, quenching, and tempering processes. The detailed process is as follows:
[0060] (1) Electric arc furnace smelting: Molten iron and steel scrap are used as raw materials, and the proportion of molten iron in the raw materials is controlled to 30% to 60%. Throughout the entire electric arc furnace smelting process, foamed slag is generated to ensure good oxidative boiling and promote the flotation of inclusions and gases in the steel. The final carbon content of the molten steel is controlled to 0.06 to 0.10%, and the tapping temperature of the molten steel is controlled to 1640 to 1680°C.
[0061] (2) LF Furnace Refining: Molten steel refined in an electric furnace is sent to the LF furnace station for refining. In the early stages of LF refining, appropriate amounts of lime and fluorite are added to form slag and improve slag fluidity. Deoxidation and desulfurization are enhanced using aluminum particles or silicon carbide, and aluminum wire is added based on the target Al content in the molten steel. The alloy composition and temperature of the molten steel are adjusted to the target requirements before tapping, ensuring the performance stability of the steel material and the temperature requirements of the continuous casting process.
[0062] (3) Vacuum refining: After LF refining, the molten steel is deslagmated and vacuum degassing is performed in a VD furnace or RH furnace. The strong stirring time under conditions of a vacuum of less than 67 Pa exceeds 10 minutes. After vacuum refining, alloying elements are added based on the chemical composition of the molten steel. Specifically, Al is added first to ensure that the free oxygen content in the molten steel is less than 5 ppm, then Ca and ferrotitanium are added, and ferroboron is added 5 to 10 minutes later to adjust the molten steel composition to the target composition. In this process, titanium wire is selected as ferrotitanium and boron wire as ferroboron to improve the alloy yield and component stability, and both are added by wire feeder. The molten steel is allowed to settle for more than 10 minutes. After the composition and temperature are satisfactory, the steel is tapped.
[0063] (4) Continuous casting: Protective injection of molten steel is employed throughout the entire process to prevent secondary oxidation and nitrogen absorption of the molten steel. Low-temperature molten steel injection is employed to control the temperature of the molten steel in the tundish to 15-30°C, electromagnetic stirring is employed in the crystallizer (mold) and at the end of solidification, and a light reduction process of 10-25 mm is employed at the end of solidification to obtain a cast slab. This reduces defects such as segregation inside the cast slab and improves the quality of the cast slab. In the continuous casting process, the continuous casting and drawing speed is 0.42-0.8 m / min, preferably 0.5-0.8 m / min, with constant drawing speed control, and the specific water content of the secondary cooling water is 0.3-0.5 L / t. The cast slab obtained by continuous casting is either supplied hot or slowly cooled in a slow cooling pit.
[0064] (5) Rolling: The cast slab is fed into a heating furnace and heated, with the heating temperature controlled to 1150-1250°C and the holding time controlled to 2-6 hours. After that, it is rolled, with the rolling start temperature controlled to ≥1100°C and the rolling end temperature controlled to ≥850°C. After rolling, the round steel is straightened and inspected for defects, and surface defects are removed by polishing. The specifications of the round steel after the above rolling are φ26-100mm. In addition, after removing the cast slab from the heating furnace, it is descaled with high-pressure water before rolling is started, and after rolling it is sent to a heat-insulating pit and slowly cooled for 24 hours or more.
[0065] (6) Quenching and tempering treatment: Quenching and tempering treatment are performed on the rolled round steel as described above. In the quenching treatment, the heating temperature is 850 to 980°C and the holding time is 1 to 4 hours. In the tempering treatment, the tempering temperature is 390 to 550°C, preferably 400 to 550°C, more preferably 400 to 450°C, and the tempering time is 1 to 3 hours. After the tempering treatment, the steel is cooled with water to room temperature. After the quenching treatment, a martensitic structure with a fine lamellar structure is formed in the steel, and the alloying elements in the steel exist in the martensite in the form of a supersaturated solid solution, so although the strength is high, the plasticity and impact toughness are relatively low. Further tempering treatment causes the supersaturated alloying elements in the martensite to disperse and precipitate between the lamellae of the martensite in the form of nano-sized carbides, which greatly improves the strength of the steel. At the same time, the occurrence of tempering brittleness can be avoided, and the chain steel obtained by the present invention has high strength and excellent impact performance.
[0066] The high-strength, high-toughness steel for mining chains and its manufacturing method according to the present invention will be described in more detail below by combining specific examples. Note that the following examples are merely for illustrating specific embodiments of the present invention and do not limit the scope of protection of the present invention in any way.
[0067] Examples
[0068] Examples 1-6
[0069] The high-strength, high-toughness mining chain steels of Examples 1-6 are manufactured by the following process:
[0070] (1) Molten steel was smelted and continuously cast according to the formulation shown in Table 1 to produce cast slabs. The manufacturing process was as follows: 1) Electric furnace smelting: The final [C] content is controlled to 0.06-0.10%, and the tapping temperature of the molten steel is controlled to 1640-1680°C. 2) LF Furnace Refining: Molten steel refined in an electric furnace is sent to the LF furnace station for refining. Deoxidation and desulfurization are enhanced using aluminum particles or silicon carbide, aluminum wire is added based on the target Al content of the molten steel, ensuring that the free oxygen content of the molten steel is less than 5 ppm, and the alloy composition and temperature of the molten steel are adjusted to meet the target requirements before tapping. 3) VD / RH Vacuum Refining Process: After LF furnace refining, the molten steel is deslagmated and vacuum degassed in a VD or RH furnace. The strong stirring time exceeds 10 minutes under conditions of a vacuum of less than 67 Pa. After vacuum refining, Al is replenished based on the chemical composition, and after ensuring that the free oxygen content in the molten steel is less than 5 ppm, Ca and ferrotitanium are added, and after 5 minutes, ferroboron is added to adjust the molten steel to the target composition. The molten steel is allowed to settle for more than 10 minutes. After the composition and temperature are satisfactory, the steel is tapped. 4) Continuous Casting: Protective injection of molten steel is employed throughout the entire process to prevent secondary oxidation and nitrogen absorption of the molten steel. Low-temperature molten steel injection is used to control the temperature of the molten steel in the tundish to 15-30°C. Electromagnetic stirring is employed in the crystallizer and at the end of solidification. A light reduction process of 10-25 mm is applied at the end of solidification to reduce defects such as segregation inside the slab and improve the quality of the slab. The continuous casting drawing speed is 0.42-0.8 m / min, with constant drawing speed control. The specific water content of the secondary cooling water is 0.3-0.5 L / t, and the slab is either supplied hot or slowly cooled in a slow-cooling pit.
[0071] (2) Rolling: The obtained slabs are sent into a heating furnace and heated, with the heating temperature of the slabs controlled to 1150-1250°C and the heating holding time controlled to 2-6 hours. During rolling, the rolling start temperature of the continuous slabs is controlled to be ≥ 1100°C and the rolling end temperature to be ≥ 850°C. After rolling, the round steel is straightened and inspected for defects, and surface defects are removed by polishing. After rolling, it is sent into a heat-insulating pit and slowly cooled for 24 hours or more.
[0072] (3) Quenching and tempering treatment: The round steel obtained by rolling is subjected to quenching and tempering treatment. The quenching temperature is 850 to 980°C and the holding time is 1 to 4 hours. The tempering temperature is 390 to 550°C and the tempering time is 1 to 3 hours. After the tempering treatment, it is cooled with water to room temperature to obtain chain steel.
[0073] Comparative Examples 1-2
[0074] In Comparative Examples 1 and 2, chain steel was manufactured using an electric furnace + LF + RH + continuous casting + quenching and tempering process. The difference lies in the fact that the composition, content, and / or process parameters of the chain steel do not conform to the present invention. For specific details, please refer to Tables 1-1, 1-2, 2-1, and 2-2.
[0075] Table 1-1 shows the chemical composition of the chain steels of Examples 1-6 and Comparative Examples 1-2.
[0076] [Table 1-1]
[0077] Table 1-2 shows the ratio of Ti / (O+2N) in the chemical composition of chain steel, and the ratio of B elements in a solid solution state to the total amount of B elements.
[0078] [Table 1-2]
[0079] Tables 2-1 and 2-2 show the parameters of the manufacturing process for chain steel in Examples 1-6 and Comparative Examples 1-2.
[0080] [Table 2-1]
[0081] [Table 2-2]
[0082] Samples were respectively taken from the steels for chains obtained in Examples 1 to 6 and Comparative Examples 1 to 2, and corresponding steel samples for chains were obtained. A tensile test and a Charpy impact test were performed on the obtained steels for chains, and performance data of the steels for chains in the Examples and Comparative Examples were acquired. The test results are shown in Table 3.
[0083] The test methods for the relevant performance parameters are as follows:
[0084] Tensile test: In accordance with the national standard GB / T 2975, samples were taken from the steels for chains of Examples 1 to 6 and Comparative Examples 1 to 2 to prepare tensile test specimens, and the tensile properties were measured in accordance with the national standard GB / T 228.1.
[0085] Charpy impact test: In accordance with the national standard GB / T 2975, samples were taken from the steels for chains of Examples 1 to 6 and Comparative Examples 1 to 2 to prepare impact test specimens, and the impact properties were measured in accordance with the national standard GB / T 229.
[0086] Table 3 shows the performance parameters of the steels for chains of Examples 1 to 6 and Comparative Examples 1 to 2.
[0087] [Table 3]
[0088] As shown in Table 3, the high-strength high-toughness steel for mining chains manufactured in Examples 1 to 6 of the present invention has excellent overall performance, with yield strength R p0.2 ≧1186MPa, tensile strength R m ≧1293MPa, elongation A≧13.5%, reduction of area Z≧50%, and room-temperature impact energy A kv ≧74J. As can be seen from this, the high-strength high-toughness steels for mining chains of Examples 1 to 6 of the present invention are clearly superior to the steels for chains of Comparative Examples 1 to 2.
[0089] As can be seen from Tables 1 and 3, compared to the chain steels of Comparative Examples 1 and 2, the high-strength, high-toughness mining chain steels of Examples 1 to 6 of the present invention have a chemical composition within the range that is intended to be protected, and achieve high strength and excellent impact toughness through an optimized quenching and tempering process.
[0090] Figure 1 is a scanning electron microscope image of the microstructure of the chain steel after quenching and tempering in Example 1. As shown in Figure 1, in Example 1, the microstructure of the chain steel after quenching and tempering is tempered martensite, with a small interlayer distance between martensite flakes and finely dispersed nanoscale carbides precipitated between the martensite lamellae. These fine nanoscale carbides significantly improve the strength and toughness of the steel, resulting in a high-strength, high-toughness mining chain steel with excellent performance.
[0091] In summary, the present invention provides a high-strength, high-toughness steel for mining chains with superior performance through a combination of rational chemical composition design and an optimized process. The chain steel of the present invention can be widely applied to fields requiring high-strength steel materials, such as marine engineering and mining machinery.
[0092] Furthermore, all technical features described herein may be freely combined or combined in any way, provided that they do not conflict with each other. It will be obvious to those skilled in the art that various modifications and changes can be made to the present invention without departing from its scope. For example, features shown or described as part of one embodiment can be used in combination with another embodiment to obtain a new embodiment. Therefore, the present invention shall encompass these modifications and changes that fall within the scope of the appended claims and their equivalents.
Claims
1. A chain steel characterized by containing, by mass%, the following chemical composition: C: 0.19-0.30%, preferably 0.20-0.30%, Si: 0.05-0.6%, preferably 0.21-0.47%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.5-0.9%, Mo: 0.3-0.55%, Ti: 0.015-0.035%, Al: 0.011-0.05%, preferably 0.02-0.05%, B: 0.0015-0.005%, N: 0.002-0.006%, with the remainder being Fe and unavoidable impurities.
2. A chain steel characterized by containing, in addition to 90% or more Fe and unavoidable impurities, the following chemical composition in mass percent: C: 0.19-0.30%, preferably 0.20-0.30%, Si: 0.05-0.6%, preferably 0.21-0.47%, Mn: 1.0-1.8%, Cr: 0.4-0.8%, Ni: 0.5-0.9%, Mo: 0.3-0.55%, Ti: 0.015-0.035%, Al: 0.011-0.05%, preferably 0.02-0.05%, B: 0.0015-0.005%, N: 0.002-0.006%.
3. The chain steel according to claim 1 or 2, characterized in that the aforementioned unavoidable impurities are P ≤ 0.012%, S ≤ 0.01%, O ≤ 0.0015%, and H ≤ 0.00015%.
4. The chain steel according to claim 3, characterized in that the chemical composition of the chain steel satisfies Ti / (O+2N) = 2 to 4, where Ti, O, and N are each the mass percentage content of the corresponding element.
5. In the aforementioned chain steel, a portion of element B exists in a solid solution state, where the ratio of element B in a solid solution state to the total amount of element B is B 固 / B 総 The chain steel according to claim 1 or 2, characterized in that the ratio is 65% to 85%.
6. The chain steel according to claim 1 or 2, characterized in that the microstructure of the chain steel is tempered martensite and carbides finely dispersed between the lamellae.
7. The steel for the chain has a yield strength Rp 0.2 ≥1150 MPa, tensile strength R m ≥1250 MPa, preferably ≥1293 MPa, elongation A ≥13%, cross-sectional shrinkage Z ≥50%, and room temperature impact energy A kv The chain steel according to claim 1 or 2, characterized in that it has performance that satisfies ≥60J.
8. (1) A process for manufacturing cast slabs by smelting and continuously casting molten steel, wherein the smelting process involves sequentially performing electric furnace smelting, LF furnace smelting, and vacuum smelting, and in the vacuum smelting process, the settling time of the molten steel before tapping exceeds 10 minutes. (2) A step of obtaining the chain steel by performing rolling, quenching, and tempering processes on the cast slab, wherein the quenching process involves a heating temperature of 850 to 980°C and a holding time of 1 to 4 hours, and the tempering process involves a tempering temperature of 390 to 550°C, preferably 400 to 550°C, more preferably 400 to 450°C, a tempering time of 1 to 3 hours, and water cooling to room temperature after the tempering process. A method for manufacturing chain steel according to any one of claims 1 to 7, characterized by including in this order.
9. The manufacturing method according to claim 8, characterized in that, in the electric furnace smelting process, molten iron and steel scrap are used as raw materials, foamed slag is generated throughout the entire electric furnace smelting process, the endpoint carbon content of the molten steel is controlled to 0.06 to 0.10%, and the tapping temperature of the molten steel is controlled to 1640 to 1680°C.
10. The manufacturing method according to claim 9, characterized in that the proportion of molten iron in the raw materials is controlled to 30 to 60% in the electric furnace smelting process.
11. The LF furnace refining process is as follows: 1) A process of adding lime and fluorite in the initial stages of LF refining to form slag; 2) A step of enhancing deoxidation and desulfurization using aluminum particles or silicon carbide, and supplementing with aluminum wire based on the target Al content in the molten steel; 3) The process of adjusting the alloy composition and temperature of the molten steel to the target required values before tapping the steel. The manufacturing method according to claim 8, characterized by including in this order.
12. The manufacturing method according to claim 8, characterized in that, in the vacuum refining process, the molten steel after LF refining is deslagmated, vacuum degassing is performed in a VD furnace or RH furnace, Al is added according to the requirements of the chemical composition of the molten steel, ensuring that the free oxygen content in the molten steel is less than 5 ppm, Ca and ferrotitanium are added, and ferroboron is added after 5 to 10 minutes to adjust the molten steel composition to the target composition.
13. The manufacturing method according to claim 12, characterized in that when vacuum degassing purification is performed in the VD furnace or RH furnace, the strong stirring time under conditions of less than 67 Pa exceeds 10 minutes.
14. The manufacturing method according to claim 12, characterized in that a titanium wire is selected for the ferrotitanium and a boron wire is selected for the ferroboron.
15. The manufacturing method according to claim 8, characterized in that, in the continuous casting process, protective injection of molten steel is employed throughout the entire process, the degree of superheating of the molten steel in the tundish is controlled to 15 to 30°C, electromagnetic stirring is employed in the crystallizer and at the end of solidification, and a light reduction process of 10 to 25 mm is employed at the end of solidification to obtain a cast slab.
16. The manufacturing method according to claim 15, characterized in that, in the continuous casting process, the continuous casting and drawing speed is 0.42 to 0.8 m / min, preferably 0.5 to 0.8 m / min, a constant drawing speed control is employed, the specific water content of the secondary cooling water is 0.3 to 0.5 L / t, and the cast slab is supplied hot or slowly cooled in a slow cooling pit.
17. The manufacturing method according to claim 8, characterized in that, in the rolling process, the cast slab is placed in a heating furnace and heated, and then rolled, with the heating temperature controlled to 1150 to 1250°C, the heating and holding time to 2 to 6 hours, the rolling start temperature to ≥ 1100°C, and the rolling end temperature to ≥ 850°C.
18. The manufacturing method according to claim 17, characterized in that, in the rolling process, the cast slab is removed from the heating furnace, descaled with high-pressure water, and then rolled, and after rolling, it is sent to a heat-insulating pit and slowly cooled for 24 hours or more.